Metamaterial assisted illumination nanoscopy via random super-resolution speckles - Yeon Ui Lee; Junxiang Zhao; Qian Ma; Larousse Khosravi Khorashad; Clara Posner; Guangru Li; G. Bimananda M. Wisna; Zachary Burns; Jin Zhang; Zhaowei Liu (Nature Communications, 2021)
Structured illumination microscopy is usually limited to 2 times spatial resolution improvement over the diffraction limit. Here, the authors introduce a metamaterial structure to generate speckle-like sub-diffraction limit illumination patterns in the near field, and achieve a 7-fold resolution improvement down to 40 nm.